Upcycling Fabric Waste for Home Decoration by Implementing Islamic Art Approach - Andi Pramono; Tiara Ika Widia Primadani; Yudhistya Ayu Kusumawati; Bambang Kartono Kurniawan; Febby Candra Pratama (Journal of Islamic Architecture, 2022)
Humanity's activities cause the destruction that occurs in the world as a caliphate, as stated in Surah Ar-Rum (30), verse 41 of the Quran. One of the products that might harm the ecosystem is waste. Various countries, including the Indonesian Government, have competed with numerous initiatives and policies to save environmental sustainability. The author of this study provided training on how to conserve the environment by processing trash, particularly fabric waste. Bina Nusantara University's community development initiative invites numerous assisted MSMEs to participate in a waste management training session. Participants are instructed on how to transform fabric waste into useful interior products. The techniques conducted start from joining fabric waste with patchwork, quilting, and applique connection techniques. From the connection results, the product's value can be increased again by adding a digital screen printing technique. Islamic Art is one of the many motifs that can be used. Implementing Islamic geometric patterns and floral, vegetal, and calligraphy designs on interior accessories are some examples of Islamic art motifs. Apart from being able to decorate the interior of the home, particularly by giving it an Islamic feel, the objective of creating this product is to conserve the environment through upcycling technology.